Intersecting marginalities: International students' struggles for "survival" in COVID‐19. Issue 4 (19th January 2021) - Coffey, Julia; Cook, Julia; Farrugia, David; Threadgold, Steven; Burke, Penny Jane
Abstract: This article draws on examples from a study of the impacts of coronavirus disease‐2019 (COVID‐19) shutdowns on young hospitality workers in Melbourne and Newcastle, Australia, in May and June of 2020. We explore how existing vulnerabilities related to gender, migrant status, and precarious hospitality work were intensified by the impacts of the COVID‐19 pandemic for young women international students in our study. The international students we discuss were exposed to extreme financial precarity, which rendered them vulnerable to other gendered forms of risk and exploitation, including taking part in experimental drug trails and having to take off‐the‐books cleaning work for a "creep." These students described feeling "unwelcome" or "unwanted" through open racial discrimination, or comments from the Prime Minister that international students should "go home." We take an embodied intersectional approach to detail how existing conditions of marginality such as gender, migrant status, economic vulnerability, and precarious conditions of hospitality labor are compounded in the pandemic and exacerbate inequalities, manifesting in increased threats to physical safety and wellbeing.